Influence of Rhenium Concentration on Charge Doping and Defect Formation in MoS2 - Kyle T. Munson; Riccardo Torsi; Fatimah Habis; Lysander Huberich; Yu‐Chuan Lin; Yue Yuan; Ke Wang; Bruno Schuler; Yuanxi Wang; John B. Asbury; Joshua A. Robinson (Advanced Electronic Materials)
Abstract Substitutionally doped transition metal dichalcogenides (TMDs) are essential for advancing TMD‐based field effect transistors, sensors, and quantum photonic devices. However, the impact of local dopant concentrations and dopant–dopant interactions on charge doping and defect formation within TMDs remains underexplored. Here, a breakthrough understanding of the influence of rhenium (Re) concentration is presented on charge doping and defect formation in MoS2 monolayers grown by metal–organic chemical vapor deposition (MOCVD). It is shown that Re‐MoS2 films exhibit reduced sulfur‐site defects, consistent with prior reports. However, as the Re concentration approaches ⪆2 atom%, significant clustering of Re in the MoS2 is observed. Ab Initio calculations indicate that the transition from isolated Re atoms to Re clusters increases the ionization energy of Re dopants, thereby reducing Re‐doping efficacy. Using photoluminescence (PL) spectroscopy, it is shown that Re dopant clustering creates defect states that trap photogenerated excitons within the MoS2 lattice, resulting in broad sub‐gap emission. These results provide critical insights into how the local concentration of metal dopants influences carrier density, defect formation, and exciton recombination in TMDs, offering a novel framework for designing future TMD‐based devices with improved electronic and photonic properties.